2021
DOI: 10.1111/1462-2920.15410
|View full text |Cite
|
Sign up to set email alerts
|

Chemical signals driving bacterial–fungal interactions

Abstract: Microorganisms reside in diverse environmental communities where interactions become indispensable due to close physical associations. These interactions are driven by chemical communication among different microbial kingdoms, particularly between fungi and bacteria. Knowledge about these communication signals provides useful information about the nature of microbial interactions and allows predictions of community development in diverse environments. Here, we provide an update on the role of small signalling … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(25 citation statements)
references
References 155 publications
1
24
0
Order By: Relevance
“…Some (e.g., cord-and rhizomorph-forming basidiomycetes), can grow through soil in search of new resources, operating foraging strategies [21], and some of these form the most extensive and persistent biological networks characterised to date [7,11,20]. with fungi producing a wide variety of signal molecules including hormones/pheromones, other small peptides, alcohols, lipids, and volatile compounds [40,[42][43][44]. Coordination and communication between the cells in a fungus facilitate complex behaviours such as pathogen colonisation of a host [45].…”
Section: Box 1 Fungal Characteristics Relevant To Behaviourmentioning
confidence: 99%
“…Some (e.g., cord-and rhizomorph-forming basidiomycetes), can grow through soil in search of new resources, operating foraging strategies [21], and some of these form the most extensive and persistent biological networks characterised to date [7,11,20]. with fungi producing a wide variety of signal molecules including hormones/pheromones, other small peptides, alcohols, lipids, and volatile compounds [40,[42][43][44]. Coordination and communication between the cells in a fungus facilitate complex behaviours such as pathogen colonisation of a host [45].…”
Section: Box 1 Fungal Characteristics Relevant To Behaviourmentioning
confidence: 99%
“…Bacterial‐fungal interactions also maintain global biogeochemical cycles and nutrient availability: lignocellulose decomposing mushrooms co‐exist with nitrogen‐fixing bacterial taxa which suggest a mutually beneficial situation of bacteria supplying nitrogen to the fungi which in return make carbon available to the bacteria (Purahong et al ., 2016). Bacterial‐fungal interactions frequently rely on low molecular weight compounds which supported drug discovery efforts as otherwise silent biosynthetic pathways for bioactive natural products are activated (Khalid and Keller, 2021). For example, the intimate contact between streptomycetes and Aspergillus nidulans hyphae was shown to transcriptionally activate a genetic locus for orsellinic acid biosynthesis (Schroeckh et al ., 2009, Nützmann et al ., 2011).…”
Section: Introductionmentioning
confidence: 99%
“…gloeosporioides (He et al ., 2020). Further, bacteria co‐cultivated with fungi can synthesize several antifungal metabolites that exhibit antagonistic activity against fungi via the chemical communication (Khalid and Keller, 2021). Carrasco and Preston (2020) also insisted the importance of cross‐talk between bacteria and fungi for crop growth and biological suppression of diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to our findings, He et al (2020) showed antifungal action of VOCs produced by B. methylotrophicus BCN2 and B. thuringiensis BCN10 in inhibiting the mycelial growth of F. oxysporum, Botryosphaeria spp., P. expansum, T. atroviride, and C. gloeosporioides (He et al, 2020). Further, bacteria cocultivated with fungi can synthesize several antifungal metabolites that exhibit antagonistic activity against fungi via the chemical communication (Khalid and Keller, 2021). Carrasco and Preston (2020) also insisted the importance of cross-talk between bacteria and fungi for crop growth and biological suppression of diseases.…”
Section: Discussionmentioning
confidence: 99%